2004
DOI: 10.1074/jbc.m401786200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Melanogenesis by Phospholipase D2 through Ubiquitin Proteasome-mediated Degradation of Tyrosinase

Abstract: The involvement of phospholipase D (PLD) in the regulation of melanogenesis was examined. Treatment of B16 mouse melanoma cells with 12-O-tetradecanoylphorbol-13-acetate (TPA) resulted in the activation of PLD and a decrease in melanin content. 1-Butanol, but not 2-butanol, completely blocked the TPA-induced inhibition of melanogenesis, suggesting the involvement of PLD in this event. Reverse transcription-PCR and immunoblot analyses revealed the existence of both PLD isozymes, PLD1 and PLD2, in B16 cells. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 49 publications
1
54
0
Order By: Relevance
“…Because melanogenic enzymes have recently been suggested to be mistargeted and degraded in Rab32/38-deficient melanocytes (Wasmeier et al, 2006), the most likely function of Varp is to control trafficking of Tyrp1 (e.g., transport from an endoplasmic reticulum [ER] to the Golgi, transport from endosomes or the trans-Golgi network, tethering, docking, and/or fusion of Tyrp1-containing vesicles to melanosomes) together with Rab32/38. In the absence of Varp, Tyrp1 is not correctly targeted to melanosomes, and mistargeted Tyrp1 (or untransported Tyrp1 in the ER) may be ubiquitinated (Ando et al, 2004(Ando et al, , 2007Kageyama et al, 2004) and degraded by proteasomes (e.g., ER-associated degradation), because our preliminary experiments showed that treatment of Varpknockdown cells (or GFP-ANKR1-expressing cells) with a proteasome inhibitor, MG132, but not with lysosomal protease inhibitors (E64d and pepstatin A), restored Tyrp1 staining (Supplemental Figure S7Af). However, treatment of cells with proteasome inhibitors also affected the morphology of the cell (i.e., change into extended and filamentous shape), which precludes us to determine the exact localization of mistargeted proteins by immunofluorescence analysis (Supplemental Figure S7A, e-h).…”
Section: Discussionmentioning
confidence: 99%
“…Because melanogenic enzymes have recently been suggested to be mistargeted and degraded in Rab32/38-deficient melanocytes (Wasmeier et al, 2006), the most likely function of Varp is to control trafficking of Tyrp1 (e.g., transport from an endoplasmic reticulum [ER] to the Golgi, transport from endosomes or the trans-Golgi network, tethering, docking, and/or fusion of Tyrp1-containing vesicles to melanosomes) together with Rab32/38. In the absence of Varp, Tyrp1 is not correctly targeted to melanosomes, and mistargeted Tyrp1 (or untransported Tyrp1 in the ER) may be ubiquitinated (Ando et al, 2004(Ando et al, , 2007Kageyama et al, 2004) and degraded by proteasomes (e.g., ER-associated degradation), because our preliminary experiments showed that treatment of Varpknockdown cells (or GFP-ANKR1-expressing cells) with a proteasome inhibitor, MG132, but not with lysosomal protease inhibitors (E64d and pepstatin A), restored Tyrp1 staining (Supplemental Figure S7Af). However, treatment of cells with proteasome inhibitors also affected the morphology of the cell (i.e., change into extended and filamentous shape), which precludes us to determine the exact localization of mistargeted proteins by immunofluorescence analysis (Supplemental Figure S7A, e-h).…”
Section: Discussionmentioning
confidence: 99%
“…Topical application of linolenic, linoleic and oleic acids (efficiency in decreasing order) produce a bleaching effect on guinea pig skin stimulated with UV light (Ando et al, 1998). As the number of melanosomes or the level of tyrosinase mRNA do not seem to be influenced, melanin inhibition by linoleic acid is probably due to a decrease of the amount of active tyrosinase inside the melanocytes because of a stimulation of tyrosinase ubiquitination and degradation by the proteasome (Ando et al, 1999(Ando et al, , 2006Kageyama et al, 2004). On contrary, those unsaturated fatty acids seem to stimulate desquamation of the skin and the stratum corneum turnover.…”
Section: Biological Agents That Interfere With Mammalian Pigmentationmentioning
confidence: 99%
“…The melanin content was determined as previously described [36,37] with minor modifications. Cells were washed with PBS, harvested by trypsinization, and centrifuged for 10 minutes at 1500 g. The cell pellets were then dissolved in 1.4 M NaOH containing 14% DMSO during 2 hours incubation at 80 ºC.…”
Section: Melanin Assaymentioning
confidence: 99%